Theoretical Perspectives on Violence against Women: a Legal Approach to the Concept of ’Sexist Terrorism’ in Spain - Moreno Martín-Pozuelo, Inés (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2019)
During the last years, the concept of sexist terrorism has gained presence in the media as a way to inform about the commission of crimes against women. However, the use of this concept lacks in providing a legal analysis. On the other side, the emergency of notions such as femicide and the social acknowledgement of sexual aggressions as a consequence of the patriarchy brings to light the need to redefine in which way those crimes are considered under the criminal law system. This research aims to analyze the legal founds in order to consider violence against women as a form of terrorism.